Political thuggery and elections in Nigeria : a case study of the 2011 general election in Bauchi State - Shehu, Mohammed Hamza (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This research analyses the challenges of political thuggery that inhibit the proper functioning of the present electoral system in the Bauchi state. It is an unfortunate practical reality that violent acts do occur during political events and election campaigns. Groups of unemployed youths are used or rather misused by politicians to intimidate and harass the opposition. This may result in the harm and/or death of innocents. Such behaviour has been a cause of much turmoil and lawlessness, underscoring the need for the introduction of effective measures to prevent such electoral threats in the upcoming elections. The study adopts a triangulation technique involving both quantitative and qualitative methods of data collection. The quantitative method involves the use of 35 close-ended questionnaires which were distributed to 380 respondents and measured against a 5.0 Likert scale. The qualitative method includes structured interviews with 10 participants to cross-check and supplements the data. The findings reveal that there was political thuggery at the Bauchi metropolis constituting the most serious challenge facing democracy. The significance of this research is to help address the problem of political thuggery as a threat to democracy in Nigeria. This research investigates the causes of the recent increase in political thuggery in the Bauchi metropolis and how it has affected the electoral process.